The bed canopy in Xenophon of Ephesus and the iconography of Mars and Venus under the Empire - Lefteratou, Anna (Ramus, 2018)
This paper discusses how Roman visual culture might be useful for deciphering the ecphrastic passages of the ancient Greek novel. Whereas ecphrasis has been one of the blossoming topics in the field, the examination of novelistic ecphrasis alongside particular works of art is still a desideratum. As a test case I will use Xenophon of Ephesus’ ecphrasis of the bed canopy depicting Ares’ and Aphrodite's embrace, in the Ephesiaca, a novel that might have been written as early as AD 65. In what follows I will argue that the scene described on the canopy would have stimulated a variety of intertexts, both literary and visual, in the minds of the imperial audience: that is, Xenophon's reader would have been encouraged to recall not just Demodocus’ song of the love of Ares and Aphrodite but also the idealised Roman version of the myth, which was so frequently depicted on frescoes and mosaics in Roman villas in the first century. I then explore Xenophon's ‘interpretatio Romana’ through the adaptations of the Ares and Aphrodite myth found in Plutarch and Lucian.